ATTRIBUTES OF MITRA IN THE AGE OF AVESTO (Scientific journal of the Fergana State University, 2023)
This article is devoted to Mithra, one of the heavenly abstract symbols of the Zoroastrian theological system, and its functions. Through artistic images, the qualities of Mithra are revealed - a powerful ruler, an excellent orator, tall, a heavenly scientist, an owner of military weapons, a virtuous, his ability to do anything. The article scientifically analyzes that the Zoroastrians proclaimed the existence of a single God and entrusted Ahura Mazda Mithra with the task of punishing apostates as the guardian of faith and beliefs at a time when it was difficult for people to imagine an all-powerful divine abstract being. Mithra leads believing countries to great victories. For happiness, he turns countries that do not keep the covenant upside down, destroys the victories they have achieved. Mithra has a hundred thousand eyes. Attributes of Mithra, such as the destruction of a hundred souls with fifty blows, a thousand souls with a hundred blows, ten thousand souls with a thousand blows, countless souls with a thousand blows, the destruction of giants who are the cause of all lies, chopping off traitors, calling the country on the path of truth to glory. Its functions are proved on the example of Sogdian written monuments of the end of the 7th - beginning of the 8th century.